Proactive professional networking strategies for enhancing teacher engagement in private school: Case study of Kraiumnuayvittaya army sponsor school - ANUTSARA SUWANWONG (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The purpose of this research is to use the case study of Kraiumnuayvittaya Army Sponsor School to develop proactive professional networking strategies for increasing teacher engagement in private schools.Methodology: Information was gathered from the school’s administrator, principal, school board members, and teachers through narrative inquiry and in-depth interviews for this phenomenological study.Findings: Proactive professional networking strategies were found to consist of (1) problem joint strategies, (2) teacher leader strategies, and (3) expertise strategies, all of which were found to increase teacher engagement in private schools. To better understand how to most effectively influence effective teacher engagement in the private school, each strategy was examined through a research and development approach within a school year.Novelty/Implications: This research’s discussed tactics were inspired by an apparent chasm between the school’s administration and its faculty. The study’s overarching goal was to shed light on how school board members, principals, and teachers at all levels perceive the school’s progress toward successfully implementing a change in teachers’ engagement.